Teaching of Portuguese Language for Foreigners: Implications of the Plurality of Concepts - Bezerra-Ferreira, J (UNESP-FACULDADE CIENCIAS & LETRAS, 2021)
The article presents preliminary results of a post-doctorate program at the Faculty of Education at the Universidade de Sao Paulo. It discusses the terminology used by universities to name the discipline Portuguese as a Foreign Language. As we know, this subject can be called additional language, heritage language, host language, among others. In this regard, the investigation seeks to understand whether there are reasons for the existence of so many denominations. In this sense, it is necessary to research whether the nomenclatures have different approaches and/or methodologies, to further understand the option to adopt them. For that, we applied a questionnaire, through Google Forms, to professors who work with the PLE in several university institutions, to know their perceptions about the subject. The results show that, in practice, most teachers do not make a difference between Portuguese Mother Tongue and Portuguese as a Foreign Language in terms of teaching approaches and are unaware of the particularities of the various existing conceptions.